A Novel Compact High-Gain Printed Quasi-Yagi Antenna and its Harmonic-Suppression Array - Zhong, Lei; Hong, Jing-Song; Zhou , Hong-Cheng (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, a novel compact printed quasi-Yagi antenna with a high gain of 8.39 dB is presented, and its binary antenna array with harmonic suppression is explored. The proposed antenna fed by a 100 Ohm coplanar stripline (CPS) achieves a 14.32 % relative bandwidth for a -10 dB reflection coefficient. The stepped impedance resonator (SIR) structure is adopted to suppress the harmonic radiations in the binary array, which is fed by a 50 Ohm coplanar waveguide (CPW). Due to its single-sided structure, this high gain antenna element and the binary array have many advantages, such as easy fabrication, compactness, low profile, and low cost. The antenna and array can be widely applied in wireless communication systems, especially in wireless power transmission (WPT) system.